Comparative study of pancreatic vessels and mesopancreas of rhesus monkeys and humans - Ye, Fan; Xiong, Hang; Su, Hongyu; Huang, Ziheng; Luo, Wenxin; Yuan, Dongmei; Yi, Tao; Zhou, Hongying (Frontiers in Surgery, 2023)
With the introduction of the concept of mesopancreas in recent years, Total Mesopancreas Excision (TMpE) based on this theory has facilitated the development of pancreatic cancer surgery in clinical practice. However, the anatomical details of the mesopancreas have not been well investigated either in human or in Rhesus monkey. In this study, 20 rhesus monkey cadavers were dissected and their mesopancreas location, relationships and arterial distribution were analyzed. We compared the location and developmental patterns of mesopancreas in macaques and humans. The results showed that the distribution of pancreatic arteries in rhesus monkeys was the same as that in humans, which is consistent with phylogenetic similarities. However, the morphological features of the mesopancreas and greater omentum is anatomically different from that of humans, including (1) the greater omentum is not connected to the transverse colon in monkeys. (2) The presence of the dorsal mesopancreas of the rhesus monkey suggests that it be an intraperitoneal organ. Comparative anatomical studies of mesopancreas and arteries in macaques and humans showed characteristic patterns of mesopancreas and similarities in pancreatic artery development in nonhuman primates, consistent with phylogenetic differentiation. The aim of our study is to compare the pancreatic vessels and fascia of human and rhesus monkeys in anatomical and embryological perspectives and to support the utilization of rhesus monkey as animal model.